Pengaruh Kompensasi, Budaya Organisasi dan Fasilitas Kerja terhadap Kinerja Karyawan pada Pt. Karimun Marine Service Tanjung Balai Karimun - Wandi, Wandi; Suhardis, Adnan (Zona Manajerial: Program Studi Manajemen (S1), 2021)
Realizing how important human resources are in the survival and progress of a company, it is natural for company owners to view human resources as more than just company assets but as partners in business. As a partner in business, the company must be fair for what human resources have given to the company. improve compensation factors, organizational culture and work facilities on employee performance. PT Karimun Marine Services has more than a decade of experience in supporting this industry with world-class services at competitive prices. The purpose of this study is to analyze the effect of compensation, organizational culture and facilities work on employee performance at PT. Karimun Marine Service The method used is multiple linear regression analysis. In this study, the population was all employees of the office of PT Karimun Marine Service Tanjung Balai Karimun, amounting to 60 people and based on this study because the population was not greater than 100 respondents, the authors took 100% of the population at PT Karimun Marine Service Tanjung. Balai Karimun as many as 60 respondents. The results of the study are partially compensation and organizational culture variables affect employee performance, partially work facilities have no effect on employee performance and simultaneously with compensation variables, organizational culture and work facilities affect employee performance.